Indicators of oral health in older adults with and without the presence of multimorbidity: a cross-sectional study - Islas-Granillo H (Dove Medical Press, 2019)
Horacio Islas-Granillo,1 Socorro Aida Borges-Yañez,2 José de Jesús Navarrete-Hernández,1 Miriam Alejandra Veras-Hernández,1 Juan Fernando Casanova-Rosado,3 Mirna Minaya-Sánchez,3 Alejandro José Casanova-Rosado,3 Miguel Ángel Fernández-Barrera,1 Carlo Eduardo Medina-Solís1,4 1Academic Area of Dentistry, Health Sciences Institute, Autonomous University of Hidalgo State, Pachuca, Mexico; 2DEPeI Faculty of Dentistry, National Autonomous University of Mexico, Ciudad de Mexico, Mexico; 3Faculty of Dentistry, Autonomous University of Campeche, Campeche, Mexico; 4Advanced Studies and Research Center in Dentistry “Dr Keisaburo Miyata”, Faculty of Dentistry, Autonomous University State of Mexico, Toluca, Mexico Purpose: The aim of this study was to determine whether there are differences in the distribution of various indicators of oral health among elderly people with and without multimorbidity (ie, two or more chronic diseases). Subjects and methods: A cross-sectional, comparative study was conducted using a sample of Mexican elderly individuals aged ≥60 years. The average age of the cohort was 79.06±9.78 years, and 69.1% were women. The variables indicating oral health were as follows: functional dentition, edentulism, hyposalivation, xerostomia, root caries and periodontitis. The multimorbidity variable was operationally categorized as follows: 0= subjects with no chronic disease or one chronic disease and 1= subjects with two or more chronic diseases. Questionnaires were used to collect information on various variables regarding general health. Likewise, the participants underwent a clinical oral examination. The analysis was performed using Stata 11.0. Results: The overall prevalence of multimorbidity was 27.3%. The prevalences of various oral health indicators were as follows: without functional dentition 89.9%; hyposalivation 59.7%; edentulism 38.9% and self-reported xerostomia 25.2%. Dental caries were observed in 95.3% of the subjects, and the prevalence of severe periodontitis was 80%. We found a significant difference only in edentulism; its prevalence was higher among subjects with multimorbidity (55.3% vs 32.7%, P=0.015) than among those without multimorbidity. Conclusion: The presence of edentulism in this sample of Mexican older adults was higher in subjects with multimorbidity. Multimorbidity and oral diseases constitute a true challenge in elderly people, because they affect quality of life and are associated with high health care costs. Keywords: older adults, multimorbidity, oral health, edentulism, tooth loss